Lgs piezoelectric crystal and its growth method

CN116103763BActive Publication Date: 2026-10-13HEFEI ZHONGKE RUIHENG NEW MATERIAL TECH CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202310122802.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-02-16
Publication Date
2026-10-13
Estimated Expiration
2043-02-16

AI Technical Summary

Technical Problem

由于LGS晶体提拉法生长工艺已经比较成熟,而离子置换的工艺复杂,可控度差,因此,提供一种新的低成本LGS压电晶体生长方法是目前需要解决的技术问题

Benefits of technology

[0021]本发明通过对LGS压电晶体生长原料进行调整并采用提拉法制备出晶体内部组分均一、无包裹体、无开裂等缺陷且直径大于80mm的LGS压电晶体,具有较高的压电性能和大尺寸优点,并且生长方法成本较低,原因主要在于:本发明采用包覆Ga2O3代替市售Ga2O3得到的晶体生长原料组分更加均一,基于二氧化硅包覆层的存在,一方面减少Ga2O3在高温下的挥发,另一方面作为包覆材料不进入新的杂质,不会对LGS晶体成品质量产生负面影响;并且不用过量配比,减少原料不必要的浪费。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116103763B_ABST
    Figure CN116103763B_ABST
Patent Text Reader

Abstract

The present application relates to a kind of LGS piezoelectric crystal and its growth method, belong to crystal growth technical field, including the following steps: Ga2O3, La2O3, SiO2 are wrapped up ingredients, briquetting, sintering, and the crystal growth raw material is obtained;Crystal growth raw material is placed in iridium gold crucible, is transferred to the furnace cavity of pulling furnace, protection gas is filled, heating to 1470-1500 ℃ to make crucible internal raw material melt, temperature is raised to 1520-1550 ℃, and heat preservation 5-10 h makes melt stable, then temperature is reduced to 1500 ℃, and LGS seed crystal that has been fixed on seed crystal rod is introduced to melt liquid level, realizes inoculation, and starts to rotate at 20-30 rpm speed, 1-1.5 mm / h pulling speed growth, after necking, shoulder expansion, equal diameter, end and in situ annealing, the LGS piezoelectric crystal that the internal component is uniform, no inclusion, no cracking and other defects and diameter is greater than 80 mm is obtained.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of crystal growth technology, specifically relating to an LGS piezoelectric crystal and its growth method. Background Technology

[0002] When some materials deform under the action of external force, opposite charges will be generated on some corresponding surfaces. This polarization phenomenon caused by the deformation of the material itself without the action of an electric field is called the positive piezoelectric effect, and such materials are called piezoelectric materials.

[0003] Lanthanum gallium silicate piezoelectric crystal (English: langasite, chemical formula: La3Ga5SiO) 14 LGS (hereinafter abbreviated as LGS) belongs to the trigonal family, 32-point group, and P321 space group. This crystal has an electromechanical coupling coefficient 2-3 times that of dry quartz, good temperature stability, and can meet the requirements of broadband SAW (Surface Acoustic Wave) devices. Furthermore, its low SAW transmission rate is beneficial for device miniaturization. This crystal is considered an important candidate material for fabricating SAW devices in next-generation mobile communication systems.

[0004] The growth method for LGS piezoelectric crystals is typically the Czochralski method, using Ga₂O₃, La₂O₃, and SiO₂ as raw materials. The crystal is grown by adjusting the ratio of these three materials. However, the high cost of Ga₂O₃ has become a bottleneck restricting the industrial application of LGS crystals, and reducing the crystal growth cost is a major problem that needs to be solved. Currently, there are two main approaches to reducing costs: one is to replace Ga in the LGS molecule with other elements; the other is to improve existing growth processes or find other more efficient growth methods. Since the Czochralski method for growing LGS crystals is relatively mature, while the ion substitution process is complex and has poor controllability, providing a new, low-cost growth method for LGS piezoelectric crystals is a technical problem that needs to be solved.

[0005] Analysis revealed that the high cost of LGS piezoelectric crystals is mainly due to the fact that Ga2O3 is more volatile than other raw materials during crystal growth, and an excessive amount of Ga2O3 is usually used. This ratio also increases production costs. Therefore, this invention obtains low-cost, high-performance LGS piezoelectric crystals by processing the raw material Ga2O3 and controlling and adjusting the growth process parameters. Summary of the Invention

[0006] The purpose of this invention is to provide an LGS piezoelectric crystal and its growth method, thereby solving the technical problems described in the background art.

[0007] The objective of this invention can be achieved through the following technical solutions:

[0008] A method for growing an LGS piezoelectric crystal includes the following steps:

[0009] The first step involves mixing, pressing, and sintering Ga2O3, La2O3, and SiO2 to obtain crystal growth raw materials.

[0010] The second step involves placing the crystal growth material in an iridium crucible, transferring the crucible to the cavity of a crystal growth pulling furnace, filling it with protective gas, heating it to 1470-1500℃ to melt the material inside the crucible, raising the temperature to 1520-1550℃, holding it at that temperature for 5-10 hours to stabilize the melt, and then cooling it to 1500℃ to introduce the LGS seed crystal, which has been fixed on the seed crystal rod, into the melt surface to achieve seeding. Growth then begins at a speed of 20-30 rpm and a pulling speed of 1-1.5 mm / h. After necking, shoulder expansion, equal diameter, tailing, and in-situ annealing, the LGS piezoelectric crystal is obtained.

[0011] Furthermore, the crystal growth raw materials are prepared through the following steps:

[0012] La2O3 was calcined at 400℃ for 0.5-1h to remove moisture and other volatiles, resulting in pretreated La2O3. The pretreated La2O3, coated Ga2O3, and SiO2 were mixed in a mass ratio of 32.6:24.3-24.7:5.4-5.6, and then placed in a mixer and stirred at 80-100 rpm for 8-10h. The mixture was then pressed into shape and sintered at 1100-1300℃ for 5-6h to obtain the crystal growth raw material.

[0013] Furthermore, the Ga2O3 coating is prepared through the following steps:

[0014] Step S1, Preparation of nano-sized Ga2O3: Dissolve Ga(NO3)3·5H2O in deionized water to make Ga 3+ The concentration was 0.01 mol / L. After adjusting the pH to 8 with ammonia, sodium dodecylbenzenesulfonate was added. After stirring and mixing, the mixture was transferred to a high-pressure reactor with a polytetrafluoroethylene liner. The mixture was heated to 140℃ and stirred for 1.5-2 hours. After cooling to room temperature, the mixture was filtered and separated. The filter cake was washed with deionized water, dried at 60℃, and then annealed at 900-1000℃ for 5 hours to obtain nano-sized Ga2O3. The ratio of sodium dodecylbenzenesulfonate to deionized water was 1.4-1.6 mmol:1L, and the mass fraction of ammonia was 25%.

[0015] Step S2: Preparation of coated Ga2O3: Place nano-sized Ga2O3 in a round-bottom flask, add anhydrous ethanol and deionized water, and adjust the pH to 8-10 with ammonia. Slowly add tetraethyl orthosilicate while stirring, and then react for 12-18 hours. After the reaction is complete, filter, wash the filter cake several times with deionized water, and dry it at 80°C to constant weight to obtain coated Ga2O3. The ratio of nano-sized Ga2O3, anhydrous ethanol, deionized water and tetraethyl orthosilicate is 5-8g:80-100mL:100mL:0.3-0.5g, and the mass fraction of ammonia is 25%.

[0016] To overcome the problem of Ga2O3's easy volatilization during crystal growth, which leads to raw material loss and increases the cost of LGS crystal growth due to excessive use, this invention prepares gallium oxide material with a silicon dioxide coating layer on its surface through a coating process. First, using inexpensive Ga(NO3)3·5H2O as raw material, high-purity, nano-sized Ga2O3 is prepared by hydrothermal precipitation. Then, under alkaline conditions, tetraethyl orthosilicate is added to hydrolyze the Ga2O3 surface to form a nano-silica coating layer. Using this material instead of commercially available Ga2O3 has the following advantages: First, the particle size is smaller, resulting in higher dispersion when mixed with La2O3 and SiO2 to prepare crystal growth raw materials, leading to a more uniform composition of the crystal growth raw materials; second, the melting point is high, and the presence of the silicon dioxide coating layer reduces the volatilization of Ga2O3 at high temperatures and does not introduce new impurities as a coating material, thus not negatively affecting the quality of the LGS crystal product; third, excessive proportions are not required, reducing unnecessary waste of raw materials.

[0017] Furthermore, the purity of La2O3 is 99.99 wt% or higher, and the purity of SiO2 is 99.99 wt% or higher.

[0018] Furthermore, the protective gas is nitrogen containing 1-2% (by volume) oxygen.

[0019] An LGS piezoelectric crystal is prepared by the above-described growth method.

[0020] The beneficial effects of this invention are:

[0021] This invention produces LGS piezoelectric crystals with uniform internal composition, no inclusions, no cracks, and a diameter greater than 80 mm by adjusting the raw materials for LGS piezoelectric crystal growth and using the Czochralski method. These crystals exhibit high piezoelectric performance and large size advantages, and the growth method has a lower cost. The main reasons for this are: the invention uses coated Ga2O3 instead of commercially available Ga2O3, resulting in a more uniform crystal growth raw material composition. The presence of the silica coating layer reduces the volatilization of Ga2O3 at high temperatures and prevents the introduction of new impurities, thus avoiding negative impacts on the quality of the finished LGS crystal. Furthermore, it avoids excessive proportions, reducing unnecessary waste of raw materials. Attached Figure Description

[0022] To more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings used in the description of the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.

[0023] Figure 1 This is an electron microscope image of the LGS piezoelectric crystal prepared in Example 1 of the present invention.

[0024] Figure 2 This is a dimensional diagram of the LGS piezoelectric crystal prepared in Example 1 of the present invention. Detailed Implementation

[0025] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0026] Example 1

[0027] A method for growing an LGS piezoelectric crystal includes the following steps:

[0028] Step 1: Calcine La2O3 at 400℃ for 0.5h to remove water and other volatiles to obtain pretreated La2O3. Prepare the pretreated La2O3, coated Ga2O3 and SiO2 in a mass ratio of 32.6:24.3:5.4. Then place them in a mixer and stir at 80rpm for 8h. Remove them, press them into shape, and sinter them at 1100℃ for 5h to obtain crystal growth raw material.

[0029] The second step involves placing the crystal growth material in an iridium crucible, transferring the crucible to the cavity of a crystal growth pulling furnace, filling it with protective gas, heating it to 1470℃ to melt the material inside the crucible, raising the temperature to 1520℃, holding it at that temperature for 10 hours to stabilize the melt, and then cooling it to 1500℃ to introduce the LGS seed crystal, which has been fixed on the seed crystal rod, into the surface of the melt to achieve seeding, and starting growth at a speed of 20 rpm and a pulling speed of 1 mm / h.

[0030] Step 3, necking: 1 hour after the crystal begins to grow, the pulling speed is changed to 3 mm / h, and the crystal diameter is made to 4 mm by heating at a rate of 4℃ / h.

[0031] Step 4, shoulder expansion: Set the lifting speed to 1mm / h and the cooling rate to 1℃ to expand the crystal diameter to 80mm. Then reduce the rotation speed to 18rpm.

[0032] Step 5, equal diameter: After the crystal diameter reaches 80mm, stabilize the crystal diameter by heating or cooling at a rate of 3℃ / h, pull it up to 80mm, pull it up at a speed of 1mm / h, and rotate it at a speed of 23rpm.

[0033] Step 6, Finishing and In-situ Annealing: Control the pulling speed to 4 mm / h, and heat at a rate of 1℃ / h until the crystal diameter is reduced from 25 mm to 20 mm after pulling. Then control the pulling speed to 60 mm / min and pull until the crystal detaches from the melt. Keep the crystal position unchanged, and reduce the melt temperature to 1300℃ at a rotation speed of 8 rpm and a cooling rate of 25℃ / h. Hold for 20 hours, and then reduce to room temperature at a cooling rate of 15℃ / h to obtain the LGS piezoelectric crystal.

[0034] The coated Ga2O3 is prepared through the following steps:

[0035] Step S1, Preparation of nano-sized Ga2O3: Dissolve Ga(NO3)3·5H2O in deionized water to make Ga 3+ The concentration was 0.01 mol / L. After adjusting the pH to 8 with ammonia, sodium dodecylbenzenesulfonate was added. After stirring and mixing, the mixture was transferred to a high-pressure reactor with a polytetrafluoroethylene liner. The mixture was heated to 140℃ and stirred for 1.5 h. After cooling to room temperature, the mixture was filtered and separated. The filter cake was washed with deionized water, dried at 60℃, and then annealed at 900℃ for 5 h to obtain nano-sized Ga2O3. The ratio of sodium dodecylbenzenesulfonate to deionized water was 1.4 mmol: 1 L, and the mass fraction of ammonia was 25%.

[0036] Step S2: Preparation of coated Ga2O3: 5g of nano-sized Ga2O3 was placed in a round-bottom flask, 80mL of anhydrous ethanol and 100mL of deionized water were added, and the pH was adjusted to 8 with ammonia. 0.3g of tetraethyl orthosilicate was slowly added while stirring, and the reaction was allowed to proceed for 12 hours. After the reaction was completed, the mixture was filtered, and the filter cake was washed several times with deionized water and dried at 80℃ to constant weight to obtain coated Ga2O3 with an ammonia mass fraction of 25%.

[0037] The purity of La2O3 is 99.99 wt%, the purity of SiO2 is 99.99 wt%, and the protective gas is nitrogen containing 1% (volume ratio) oxygen.

[0038] The LGS piezoelectric crystal prepared in Example 1 was tested, and the results are as follows: Figure 1 and Figure 2 As shown, its internal components are homogeneous, without inclusions, cracks or other defects, and its diameter is 81.48 mm. A quasi-static d-axis was used. 33 The measuring instrument measured the d of the LGS piezoelectric crystal. 11 =6.3, d 14 = -5.4.

[0039] Example 2

[0040] A method for growing an LGS piezoelectric crystal includes the following steps:

[0041] Step 1: Calcine La2O3 at 400℃ for 0.8h to remove water and other volatiles to obtain pretreated La2O3. Prepare the pretreated La2O3, coated Ga2O3 and SiO2 in a mass ratio of 32.6:24.5:5.5. Then place them in a mixer and stir at 90rpm for 9h. Remove them, press them into shape, and sinter them at 1200℃ for 5.5h to obtain crystal growth raw material.

[0042] The second step involves placing the crystal growth material in an iridium crucible, transferring the crucible to the cavity of a crystal growth pulling furnace, filling it with protective gas, heating it to 1480℃ to melt the material inside the crucible, raising the temperature to 1530℃, holding it at that temperature for 8 hours to stabilize the melt, and then cooling it to 1500℃ to introduce the LGS seed crystal, which has been fixed on the seed crystal rod, into the surface of the melt to achieve seeding, and starting growth at a speed of 25 rpm and a pulling speed of 1.3 mm / h.

[0043] Step 3, necking: 1 hour after the crystal begins to grow, the pulling speed is changed to 4 mm / h, and the crystal diameter is made to 5 mm by heating at a rate of 4℃ / h.

[0044] Step 4, shoulder expansion: Set the lifting speed to 1mm / h and the cooling rate to 1℃ to expand the crystal diameter to 80mm. Then reduce the rotation speed to 18rpm.

[0045] Step 5, equal diameter: After the crystal diameter reaches 80mm, stabilize the crystal diameter by heating or cooling at a rate of 3℃ / h, pull it up to 80mm, pull it up at a speed of 1mm / h, and rotate it at a speed of 23rpm.

[0046] Step 6, Finishing and In-situ Annealing: Control the pulling speed to 4 mm / h, and heat at a rate of 1℃ / h until the crystal diameter is reduced from 25 mm to 20 mm after pulling. Then control the pulling speed to 60 mm / min and pull until the crystal detaches from the melt. Keep the crystal position unchanged, and reduce the melt temperature to 1300℃ at a rotation speed of 8 rpm and a cooling rate of 25℃ / h. Hold for 20 hours, and then reduce to room temperature at a cooling rate of 15℃ / h to obtain the LGS piezoelectric crystal.

[0047] The coated Ga2O3 is prepared through the following steps:

[0048] Step S1, Preparation of nano-sized Ga2O3: Dissolve Ga(NO3)3·5H2O in deionized water to make Ga 3+ The concentration was 0.01 mol / L. After adjusting the pH to 8 with ammonia, sodium dodecylbenzenesulfonate was added. After stirring and mixing, the mixture was transferred to a high-pressure reactor with a polytetrafluoroethylene liner. The mixture was heated to 140℃ and stirred for 1.8 h. After cooling to room temperature, the mixture was filtered and separated. The filter cake was washed with deionized water, dried at 60℃, and then annealed at 950℃ for 5 h to obtain nano-sized Ga2O3. The ratio of sodium dodecylbenzenesulfonate to deionized water was 1.5 mmol: 1 L, and the mass fraction of ammonia was 25%.

[0049] Step S2: Preparation of coated Ga2O3: 7g of nano-sized Ga2O3 was placed in a round-bottom flask, 90mL of anhydrous ethanol and 100mL of deionized water were added, and the pH was adjusted to 8 with ammonia. 0.4g of tetraethyl orthosilicate was slowly added while stirring, and the reaction was allowed to proceed for 12 hours. After the reaction was completed, the mixture was filtered, and the filter cake was washed several times with deionized water and dried at 80℃ to constant weight to obtain coated Ga2O3 with ammonia mass fraction of 25%.

[0050] The purity of La2O3 is 99.99 wt%, the purity of SiO2 is 99.99 wt%, and the protective gas is nitrogen containing 1-2% (volume ratio) oxygen.

[0051] The LGS piezoelectric crystal prepared in Example 2 was tested and found that its internal components were uniform, without inclusions, cracks or other defects, and its diameter was 81.52 mm.

[0052] Example 3

[0053] A method for growing an LGS piezoelectric crystal includes the following steps:

[0054] Step 1: Calcine La2O3 at 400℃ for 1 hour to remove moisture and other volatiles to obtain pretreated La2O3. Prepare the pretreated La2O3, coated Ga2O3 and SiO2 in a mass ratio of 32.6:24.7:5.6. Then place the mixture in a mixer and stir at 100 rpm for 10 hours. Remove the mixture, press it into shape, and sinter it at 1300℃ for 6 hours to obtain the crystal growth raw material.

[0055] The second step involves placing the crystal growth material in an iridium crucible, transferring the crucible to the cavity of a crystal growth pulling furnace, filling it with protective gas, heating it to 1500℃ to melt the material inside the crucible, raising the temperature to 1550℃, holding it at that temperature for 10 hours to stabilize the melt, and then cooling it to 1500℃ to introduce the LGS seed crystal, which has been fixed on the seed crystal rod, into the surface of the melt to achieve seeding, and starting growth at a speed of 30 rpm and a pulling speed of 1.5 mm / h.

[0056] Step 3, necking: 1 hour after the crystal begins to grow, the pulling speed is changed to 5 mm / h, and the crystal diameter is made to 6 mm by heating at a rate of 4℃ / h.

[0057] Step 4, shoulder expansion: Set the lifting speed to 1mm / h and cool down at a rate of 2℃ to expand the crystal diameter to 80mm. Then reduce the rotation speed to 18rpm.

[0058] Step 5, equal diameter: After the crystal diameter reaches 80mm, stabilize the crystal diameter by heating or cooling at a rate of 3℃ / h, pull it up to 80mm, pull it up at a speed of 1mm / h, and rotate it at a speed of 23rpm.

[0059] Step 6, Finishing and In-situ Annealing: Control the pulling speed to 4 mm / h, and heat at a rate of 3℃ / h until the crystal diameter is reduced from 25 mm to 20 mm after pulling. Then control the pulling speed to 60 mm / min and pull until the crystal detaches from the melt. Keep the crystal position unchanged, and reduce the melt temperature to 1300℃ at a rotation speed of 8 rpm and a cooling rate of 25℃ / h. Hold for 20 hours, and then reduce to room temperature at a cooling rate of 15℃ / h to obtain the LGS piezoelectric crystal.

[0060] The coated Ga2O3 is prepared through the following steps:

[0061] Step S1, Preparation of nano-sized Ga2O3: Dissolve Ga(NO3)3·5H2O in deionized water to make Ga 3+The concentration was 0.01 mol / L. After adjusting the pH to 8 with ammonia, sodium dodecylbenzenesulfonate was added. After stirring and mixing, the mixture was transferred to a high-pressure reactor with a polytetrafluoroethylene liner. The mixture was heated to 140℃ and stirred for 2 hours. After cooling to room temperature, the mixture was filtered and separated. The filter cake was washed with deionized water, dried at 60℃, and then annealed at 1000℃ for 5 hours to obtain nano-sized Ga2O3. The ratio of sodium dodecylbenzenesulfonate to deionized water was 1.6 mmol: 1 L, and the mass fraction of ammonia was 25%.

[0062] Step S2: Preparation of coated Ga2O3: Place 8g of nano-sized Ga2O3 in a round-bottom flask, add 100mL of anhydrous ethanol and 100mL of deionized water, and adjust the pH to 8 with ammonia. Slowly add 0.5g of tetraethyl orthosilicate while stirring, and then react for 12h. After the reaction is complete, filter, wash the filter cake several times with deionized water, and dry it at 80℃ to constant weight to obtain coated Ga2O3 with an ammonia mass fraction of 25%.

[0063] The purity of La2O3 is 99.99 wt%, the purity of SiO2 is 99.99 wt%, and the protective gas is nitrogen containing 1-2% (volume ratio) oxygen.

[0064] The LGS piezoelectric crystal prepared in Example 3 was tested and found that its internal components were uniform, without inclusions, cracks or other defects, and its diameter was 81.55 mm.

[0065] In the description of this specification, the references to terms such as "an embodiment," "example," "specific example," etc., indicate that a specific feature, structure, material, or characteristic described in connection with that embodiment or example is included in at least one embodiment or example of the present invention. In this specification, the illustrative expressions of the above terms do not necessarily refer to the same embodiment or example. Furthermore, the specific features, structures, materials, or characteristics described may be combined in any suitable manner in one or more embodiments or examples.

[0066] The above description is merely an example and illustration of the concept of the present invention. Those skilled in the art can make various modifications or additions to the specific embodiments described or use similar methods to replace them, as long as they do not deviate from the concept of the invention or exceed the scope defined in the claims, they should all fall within the protection scope of the present invention.

Claims

1. A method for growing an LGS piezoelectric crystal, characterized in that, Includes the following steps: The first step involves mixing, pressing, and sintering Ga2O3, La2O3, and SiO2 to obtain crystal growth raw materials. The second step involves placing the crystal growth material in an iridium crucible, transferring the crucible to the cavity of a crystal growth pulling furnace, filling it with protective gas, heating it to 1470-1500℃ to melt the material inside the crucible, raising the temperature to 1520-1550℃, holding it at that temperature for 5-10 hours to stabilize the melt, and then cooling it to 1500℃ to introduce the LGS seed crystal, which has been fixed on the seed crystal rod, into the melt surface to achieve seeding. The crystal then begins to grow at a speed of 20-30 rpm and a pulling speed of 1-1.5 mm / h. After necking, shoulder expansion, equal diameter, tailing, and in-situ annealing, the LGS piezoelectric crystal is obtained. The coated Ga2O3 is prepared through the following steps: Step S1: Dissolve Ga(NO3)3·5H2O in deionized water to make Ga 3+ The concentration was 0.01 mol / L. After adjusting the pH to 8 with ammonia, sodium dodecylbenzenesulfonate was added. After stirring and mixing, the mixture was transferred to a reaction vessel and stirred at 140℃ for 1.5-2 h. After cooling to room temperature, the mixture was filtered and separated. After washing and drying, it was annealed at 900-1000℃ for 5 h to obtain nano-sized Ga2O3. Step S2: Place nano-sized Ga2O3 in a round-bottom flask, add anhydrous ethanol and deionized water, and adjust the pH to 8-10 with ammonia. Slowly add tetraethyl orthosilicate while stirring, and then react for 12-18 hours. After the reaction is complete, filter, wash and dry to obtain coated Ga2O3.

2. The method for growing an LGS piezoelectric crystal according to claim 1, characterized in that, Crystal growth raw materials are prepared through the following steps: La2O3 was calcined at 400℃ for 0.5-1h to obtain pretreated La2O3. The pretreated La2O3, coated Ga2O3 and SiO2 were mixed in a mass ratio of 32.6:24.3-24.7:5.4-5.6 and stirred at 80-100rpm for 8-10h. The mixture was then pressed into shape and sintered at 1100-1300℃ for 5-6h to obtain the crystal growth raw material.

3. The method for growing an LGS piezoelectric crystal according to claim 1, characterized in that, In step S1, the ratio of sodium dodecylbenzenesulfonate to deionized water is 1.4-1.6 mmol: 1 L.

4. The method for growing an LGS piezoelectric crystal according to claim 1, characterized in that, In step S2, the ratio of nano-sized Ga2O3, anhydrous ethanol, deionized water, and tetraethyl orthosilicate is 5-8g: 80-100mL: 100mL: 0.3-0.5g.

5. The method for growing an LGS piezoelectric crystal according to claim 1, characterized in that, The protective gas is nitrogen containing 1-2% oxygen by volume.

6. The method for growing an LGS piezoelectric crystal according to claim 1, characterized in that, The purity of La2O3 is 99.99wt% or higher, and the purity of SiO2 is 99.99wt% or higher.

Citation Information

Patent Citations

  • Method for preparing gallium lanthanum niobate series nano powder

    CN101190798A

  • Manufacturing method for langasite piezoelectric crystal and product thereof

    CN103911662A

  • Preparation method of wide-temperature-range antioxidant silicon dioxide coated molybdenum disilicide powder

    CN115285997A